2009
DOI: 10.1080/10495390903004493
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Sexual Precocity and Alleles ofKISS-1andGPR54Genes in Goats

Abstract: KISS-1 and GPR54 were regarded as key regulators for the puberty onset and fundamental gatekeepers of sexual maturation in mammals. To explore the possible association between variations in KISS-1 and GPR54 with sexual precocity, mutation screening of exon 1 of KISS-1 and exon 1, exon 3, and partial exon 5 of GPR54 was performed in a sexual precocious breed (Jining Grey goats) and sexual late-maturing breeds (Inner Mongolia Cashmere, Angora, and Boer goats) by PCR-SSCP. The results showed that five novel mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
2
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 15 publications
1
11
2
2
Order By: Relevance
“…Recently, eleven novel SNPs were identified in a study on three goat breeds . Various studies (Cao et al, 2010;Feng et al, 2001) including the present one did not find mutation in exon 2, which may reflect the fact that exon 2 is important for the function of KiSS1 gene and is evolutionarily conserved. It's worth mentioning that three (G296C, G455T and T505A) out of the nine mutations identified in the present study correspond to the mutations reported in intron 1 by Cao et al (2010).…”
Section: Snp Identification and Genotypingcontrasting
confidence: 42%
“…Recently, eleven novel SNPs were identified in a study on three goat breeds . Various studies (Cao et al, 2010;Feng et al, 2001) including the present one did not find mutation in exon 2, which may reflect the fact that exon 2 is important for the function of KiSS1 gene and is evolutionarily conserved. It's worth mentioning that three (G296C, G455T and T505A) out of the nine mutations identified in the present study correspond to the mutations reported in intron 1 by Cao et al (2010).…”
Section: Snp Identification and Genotypingcontrasting
confidence: 42%
“…In Jining Grey goat KISS1 gene, there are two mutations (G3433A and C3688A) in exon 3, three mutations (G296C, G454T and T505A) in intron 1 and an 18 bp deletion/insertion (1960–1977) in intron 2 and no mutations in exon 2 [23]. Feng et al (2009) detected the polymorphism in exon 2 of goat KISS1 gene and did not find polymorphism [24]. In the current study, ten polymorphisms were detected in KISS1 gene of three goat breeds (g.1147T>C, g.1417G>A, g.1428_1429delG, g.2124C>T, g.2270C>T, g.2489T>C, g.2510G>A, g.2540C>T, g.3864_3865delCA and g.3885_3886insACCCC).…”
Section: Discussionmentioning
confidence: 99%
“…Kisspeptin sebagai regulator hulu esensial neuron yang mensekresikan GnRH (gonadotropin-releasing hormone), nodus hipotalamus utama untuk kontrol stimulasi sumbu HPG (hypothalamic-pituitary-gonadal). Menurut Feng et al (2009) KISS1 dan GPR54 merupakan regulator kunci untuk awal pubertas dan penjaga gerbang fundamental dewasa kelamin pada mamalia.…”
Section: Pendahuluanunclassified
“…Gen KISS1 (exon 1) pada kambing PE betina induk penelitian tidak dapat dijadikan sebagai biomarker untuk fekunditas kambing PE. Hasil ini bersesuaian dengan Feng et al (2009) yang melaporkan bahwa polimorfisme tidak terdeteksi pada gen KISS1 (exon 1) pada kambing Jining Gray, Mongolia Cashmere, Angora, dan Boer melalui PCR-SSCP, sehingga tidak ada kaitan antara gen ini dengan litter size.…”
Section: Gen Kiss1 (Exon 1)unclassified